Amyloid β: Walking on the dark side of the moon. (December 2015) - Fedele, Ernesto; Rivera, Daniela; Marengo, Barbara; Pronzato, Maria A.; Ricciarelli, Roberta
Highlights: Aβ is physiologically produced in the brain. Aβ is necessary for the expression of LTP and for memory formation. cAMP is required for LTP and memory. cAMP stimulates Aβ production that is needed for LTP and memory. Aβ physiological functions need to be unravelled to better understand Alzheimer's disease. Abstract: For some decades, amyloid β (Aβ) has only been considered as a cytotoxic peptide, putative cause and marker of Alzheimer's disease (AD). Today, however, a considerable amount of evidence goes against the classical amyloid hypothesis and illustrates a new picture in which the Aβ loss of function, rather than its accumulation, has a pathogenic role in AD. In this concise review, we summarize some highlights of a collection of research pointing to the physiological function of Aβ and its role in the mechanisms of memory formation.